A new combination and taxonomic update for Gyptis oblongifolia (Asteraceae) - Rebouças, Natanael Costa; Amorim, Vivian Oliveira; Grossi, Mariana Andrea; Roque, Nádia; Bünger, Mariana De Oliveira (Phytotaxa, 2025)
Historically, Eupatorium oblongifolium (Spreng.) Baker is a species that has undergone several recombinations, synonymizations and description of varieties, but no review work has been developed with the aim of solving its taxonomic and nomenclatural problems. Therefore, during the taxonomic review of the genus Stomatanthes (Asteraceae, Eupatorieae) in South America, we found it necessary to propose adjustments, as recommended by the International Code of Botanical Nomenclature (ICNB). After analyzing protologues, type materials and approximately 50 specimens stored in 17 herbaria, a new name, typifications, synonymizations, and updates in the description and geographic distribution and conservation status of the species were proposed.